Analisis Pengaruh Tingkat Pendidikan dan Pemahaman Wajib Pajak Terhadap Kesadaran Wajib Pajak Orang Pribadi Pada KPP Pratama Serpong - Hartati, Nike Nur; Rahmawati, Titah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to examine the influence of education level and taxpayer understanding on individual taxpayer awareness, both simultaneously and partially. Data were collected through a questionnaire, and the analysis was conducted using multiple linear regression with purposive sampling. The sample consisted of 100 respondents who were taxpayers with employee status. The findings of this study reveal that: (1) Based on the F-test, the variables of education level and taxpayer understanding simultaneously affect taxpayer awareness. The calculated F-value of 52.279 is greater than the F-table value of 3.09, indicating that the regression model significantly explains the variance in the dependent variable. (2) Based on the t-test, the education level variable has a significant effect on individual taxpayer awareness, with a significance level of <0.001 (<0.05). (3) Based on the t-test, the taxpayer understanding variable also has a significant effect on individual taxpayer awareness, with a significance level of <0.001 (<0.05).